Performa 13. - Goldberg, RoseLee; Hoffmann, Jens; Edwards, Adrienne; Ögüt, Ahmet (New York : Performa, 2015)
Althamer, Pawel ; Johnson, Rashid ; McNamara , Ryan ; Gupta, Subodh ; Hecker, Florian ; Singh, Alexandre ; Barba, Rosa ; Peake, Eddie ; Lutker, Shana ; Vitale, Marianne ; Raqs Media Collective ; Wranes, Tori ; Spooner, Cally ; Amir, Einat ; Jonas, Joan ; Bel, Jérôme ; Hassabi, Maria ; Lowe, Molly ; Meier, Dieter ; Charmatz Boris
boek